The properties of an improvised piston pump for the rapid delivery of intravenous fluids1. (3rd January 2014) - Smart, C. M.; Primrose, C. W.; Peters, A. L.; Speirits, E. J.
Summary To maximise the effect of a small fluid load, it is occasionally desirable to bolus manually with multiple depressions of a large‐capacity syringe. This is usually achieved by placing the syringe on the side port of a three‐way tap. We modified this technique by placing two‐one‐way valves in line with the three‐way tap, effectively creating a piston pump, the infusion rates via which we compared with those achieved by an inflatable pressure‐infuser in a simulated resuscitation. Fluid flow was faster using the piston pump than with the pressure‐infuser (mean (SD) time to infuse 2000 ml saline 0.9% via a 16‐G cannula 352 (10) s vs 495 (19) s, respectively, p < 0.0001). The piston pump appears to have potential for both tight control of fluid delivery and major high‐volume resuscitation. The lightweight nature of the pump and its lack of reliance on gravity may also make it suitable for the pre‐hospital setting.